Operating Expenses Ratio (OER) and Total Asset Turnover (TATO) to Return on Assets (ROA) - Putri, Reyningrum Camilda; Pardistya, Irvan Yoga; Liana, Siska (Ekonomi, Keuangan, Investasi dan Syariah (EKUITAS), 2026)
This quantitative study investigates the "profitless growth" phenomenon to empirically examine the financial determinants of profitability within the food and beverage manufacturing subsector. Specifically, the research analyzes the extent to which the Operating Expense Ratio (OER) and Total Asset Turnover (TATO) impact Return on Assets (ROA). The study relies on secondary data derived from 13 companies listed on the Indonesia Stock Exchange (IDX), covering an observation period from 2014 to 2024. Data processing was executed using IBM SPSS Statistics software through a multiple linear regression model. The empirical results reveal that OER exerts a significant positive influence on ROA (Sig < 0.001), indicating that operational expenditures in this sector function as productive investments rather than mere costs. Similarly, TATO demonstrates a significant positive impact (Sig = 0.049), confirming that efficient asset utilization is crucial for maximizing earnings. Furthermore, the simultaneous analysis confirms that these independent variables collectively affect profitability, accounting for 62.5% of the variance in ROA ( = 0.625). These findings highlight the critical importance of synergizing strategic operational spending with aggressive asset rotation to sustain corporate profitability amidst economic volatility.